Highly microporous SbPO4/BCx hybrid anodes for sodium-ion batteries. Issue 2 (17th April 2020) - Wang, Huiqi; Gou, Li; Jing, Weifeng; An, Duo; Li, Ying; Wang, Mei; Li, Ning; Hu, Shengliang; He, Yan-Bing
Abstract : An easy route was developed to fabricate a highly microporous SbPO4 /BC x hybrid anode for high-performance sodium-ion batteries. Abstract : The current anode materials greatly restrict the electrochemical performance of sodium-ion batteries. Herein, we propose a highly microporous SbPO4 /BC x hybrid anode for sodium-ion batteries, exhibiting a high initial reversible capacity of 871 mA h g −1 at 50 mA g −1, a good rate capability of around 300 mA h g −1 even at 5 A g −1 as well as an excellent cycling stability of 500 cycles. The excellent rate capability and cyclability with high capacity are probably due to the novel BC x structure and stable PO4 3− anions. The abundant micropores serve as reservoirs for storing the sodium ions and shorten the diffusion distance. The high surface area contributes to ample contact area between the electrode and electrolyte, thus achieving a rapid charge-transfer reaction. XPS analysis reveals that the BC x matrix consists of three B/C structures of BC3, BC2 O, and BCO2, and contains around 12.93 at% substitutional boron. Since valence band holes are created by the B/C structures, more sodium ions would be captured easily, which motivates more sodium ions to intercalate electrochemically. Additionally, both the robust BC x matrix and stable PO4 3− anions as buffers could accommodate the volumetric expansion during the sodium ion insertion, thus optimizing the cycling performance. The strong attachment between SbPO4 and the BC x matrix would benefit mutual charge transfer between them and keep the integrity of the electrode during the sodiation/desodiation processes, which are favorable for sodium-ion transport and play a crucial role in enhancing the rate performance. Accordingly, the SbPO4 /BC x composite is expected to become a promising anode for advanced SIBs.